HUBUNGAN KEPUASAN KERJA DENGAN ABSENSI KARYAWAN PADA DIVISI PERTAMBANGAN PT X - Salman Ahmad Effendi & Muslimah Zahro Romas (Jurnal Psikologi, 2014)
Objective of this research is to verify the relationship between job satisfaction and absenteeism among mining employees. Employees with high percentage of absenteeism tend to have low job satisfaction. Absenteeism reflects low morale in organization. Unsatisfied employees tend to withdrawal from various organization programs; fail to report about their attendance, and having negative attitude toward organization. The hypothesis is that there is negative relationship between job satisfaction and employee's absenteeism. The more they satisfy with their jobs, the lower their absenteeism level. Ten employees participated in this research. According to the human resource division, those employees were often absenteeism. Therefore were requested to fill in the Job Satisfaction Scale. Thus the dependent variable is the absenteeism level and the independent variable is employees' job satisfaction. This research revealed that there is no relationship between job satisfaction and absenteeism (the Spearman Correlation Rho = -0.190, p<0.05). Two research limitations are discussed.